The communicative approach to teaching a foreign language - Arina V. Banartseva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The Communicative Approach emphasizes the ability to communicate the meaning of the message, instead of concentrating on grammatical perfection. It emerged in 1960s and is still actual today. The approach focuses on authentic communication and negotiating meaning. Its main characteristic is understanding of English through active student interaction; role play, games, information gaps. Communicative competence applies to both spoken and written language and it is the progressive acquisition of the ability to use a language to achieve one's goals. Communicative competence represents a shift in focus from the grammatical to the communicative properties of the language; i.e. the functions of language and the process of discourse. The communicative approach is based on the idea that successfully comes through having to communicate real meaning. When learners are involved in real communication, their natural strategies for will be used, and this will allow them to learn to use the language.